Behaviour of plug-and-play joints between RHS columns and CFS trusses. (July 2022) - Tankova, Trayana; Craveiro, Hélder; Silva, Luís Carlos; Ribeiro, Fernando F.; Simões, Rui; Martins, Claúdio; Costa, Ricardo; Simões da Silva, Luís
Abstract: Steel tubular members are efficient and aesthetic structural solution, yet the bolted connections between then are challenging due to the restricted access to the inside of the tube. There are several solutions, which try to overcome this difficulty, by adoption of special fasteners and/or additional connecting elements. This paper presents the experimental and numerical characterization of a novel plug-and-play joint that was developed as a demountable solution to connect tubular steel columns to cold-formed steel trusses. The research program comprised a large number of experimental tests on components and the full-scale joints, complemented by numerical models calibrated with the experimental tests. These calibrated numerical models were subsequently used to perform a large parametric study on the components and joint that allowed to propose guidelines on the geometries that maximise the performance of these joints.